2015
DOI: 10.2337/db15-0527
|View full text |Cite
|
Sign up to set email alerts
|

Human Insulinomas Show Distinct Patterns of Insulin Secretion In Vitro

Abstract: Insulinomas are β-cell tumors that cause hypoglycemia through inappropriate secretion of insulin. Characterization of the in vitro dynamics of insulin secretion by perifused fragments of 10 human insulinomas permitted their subdivision into three functional groups with similar insulin content. Group A (four patients with fasting and/or postprandial hypoglycemic episodes) showed qualitatively normal responses to glucose, leucine, diazoxide, tolbutamide, and extracellular CaCl2 omission or excess. The effect of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 47 publications
(83 reference statements)
0
5
0
Order By: Relevance
“…Moreover, some reports contended that insulin resistance was found in insulinoma due to the defect in peripheral glucose utilisation 20 21. Some reported that human insulinomas in vitro show distinct defects in insulin secretion 22. Therefore, the concurrent insulinoma and impaired glucose tolerance might not be as rare as once thought.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, some reports contended that insulin resistance was found in insulinoma due to the defect in peripheral glucose utilisation 20 21. Some reported that human insulinomas in vitro show distinct defects in insulin secretion 22. Therefore, the concurrent insulinoma and impaired glucose tolerance might not be as rare as once thought.…”
Section: Discussionmentioning
confidence: 99%
“…However, in the presence of an insulinoma, this glucose-insulin coupling becomes dysregulated. Small-scale in vitro studies have shown that cultured human insulinoma cells can have near maximal glucose responsiveness at blood glucose levels of 1.0–3.0 mmol/L ( 19 ) with no significant increase in insulin release with rise in glucose concentration from 2.8 to 8.3 mmol/L in one study ( 20 ) and plateau at 10.0–15.0 mmol/L in two other studies ( 19 , 21 ). The autonomous insulin secretion despite low glucose concentrations and the blunted insulin response to higher glucose concentrations can give rise to fasting hypoglycemia and postprandial hyperglycemia, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Insulinomas represent a heterogenous group of tumors that show a different secretory behavior, for example, due to changes in the growth behavior of beta cells, abnormalities in the somatostatin receptor expression, or the exocytosis of the insulin granules [27]. In addition, the presence of hexokinase I enables the secretion of insulin at low blood sugar levels in some insulinomas [28]. Boden et al put forward the theory that insulinomas mainly show glucose transporter type 1 (GLUT1) expression and healthy beta cells, mainly GLUT2 [29].…”
Section: Discussionmentioning
confidence: 99%